STUDENTS’ PERCEPTION ABOUT THE USE OF SELF-ASSESSMENT IN WRITING SKILL AT SMK NEGERI 2 SINGARAJA - Made Andini Putri Adelia; A.A. Gede Yudha Paramartha; Ni Luh Putu Eka Sulistia Dewi; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2024)
This research aimed to investigate how students viewed self-assessment of their writing skill and to determine the challenges students faced during the process of self-assessment of their writing skill. This research used a survey research design with a qualitative approach that enriches with quality. The participants involved were 10th grade students majoring in tourism at SMK Negeri 2 Singaraja. The participants in this research were 111 students from three different classes, namely class X-AP 3 with 37 students, class X-AP4 with 37 students, and class X-AP5 with 37 students. Open-ended questionnaires and interviews were conducted to collect the necessary data. Data were analyzed using thematic analysis for qualitative data obtained from interviews, and descriptive statistics were used to summarize responses from open-ended questionnaires. The research results show that there are indications that students tend to have a positive perception of self-assessment of their writing skill. It is found that with self-assessment, students can improve their writing skills, encourage motivation, achieve goals, fulfill their expectations in writing, and can help students assess their own writing results. Apart from that, there are also challenges faced by students, such as a lack of objective attitude in carrying out self-assessments and the emergence of feelings of confusion when carrying out self-assessments. This is caused by the students' lack of experience in carrying out self-assessments and the students' lack of honesty in carrying out self-assessments regarding writing skills.